The prevalence of impulsive compulsive behaviors in patients treated with apomorphine infusion: a retrospective analysis - Barbosa, Pedro; Djamshidian, Atbin; Lees, Andrew John; Warner, Thomas Treharne (Arquivos de Neuro-Psiquiatria, 2022)
Background: Impulsive compulsive behaviors (ICBs) can affect a significant number of Parkinson’s disease (PD) patients. Objective: We have studied brain samples from a brain bank of PD patients who received apomorphine via continuous infusion in life to assess the prevalence and outcome of ICBs. Methods: A search on the Queen Square Brain Bank (QSBB) database for cases donated from 2005 to 2016 with a pathological diagnosis of idiopathic PD was conducted. Notes of all donors who used apomorphine via continuous infusion for at least three months were reviewed. Clinical and demographic data were collected, as well as detailed information on treatment, prevalence and outcomes of ICBs. Results: 193 PD cases, 124 males and 69 females, with an average age at disease onset of 60.2 years and average disease duration of 17.2 years were reviewed. Dementia occurred in nearly half of the sample, depression in one quarter, and dyskinesias in a little over 40%. The prevalence of ICBs was 14.5%. Twenty-four individuals used apomorphine infusion for more than three months. Patients on apomorphine had younger age at disease onset, longer disease duration, and higher prevalence of dyskinesias. The prevalence of de novo ICB cases among patients on apomorphine was 8.3%. Apomorphine infusion was used for an average of 63.1 months on an average maximum dose of 79.5 mg per day. Ten patients remained on apomorphine until death. Conclusions: Apomorphine can be used as an alternative treatment for patients with previous ICBs as it has low risk of triggering recurrence of ICBs.
Keywords: Parkinson Disease; Compulsive Behavior; Impulsive Behavior; Disruptive, Impulse Control, and Conduct Disorders; Apomorphine